MICROPLASTICS IN INDONESIAN AGRICULTURE: CRITICAL INSIGHTS AND THE ROLE OF FUNGAL BIOREMEDIATION FOR ENVIRONMENTAL SUSTAINABILITY - Alfarisy, Fariz Kustiawan; Hoesain, Mohammad (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Microplastics are emerging pollutants derived from plastic waste and materials that undergo fragmentation processes. Their presence poses significant threats not only to environmental sustainability but also to human health. Agriculture, among other sectors, is increasingly affected by microplastic contamination, with potential implications for agricultural product quality and food safety. This study aimed to assess the status of microplastic contamination in Indonesian agriculture and to explore bioremediation strategies for sustainable environmental management. Literature review was conducted following the PRISMA framework using publications retrieved from the Scopus and Semantic Scholar databases. Research trends and thematic focuses were visualized using VOSviewer, while case studies on microplastic abundance in agricultural areas of Indonesia were analyzed using Python. The review revealed that microplastics have been widely distributed across several agricultural regions in Indonesia. Based on the synthesis of findings from the literature review and various case studies, polyethylene and polypropylene were identified as the predominant microplastic polymers detected in agricultural environments. In addition, several beneficial fungal species, including strains originating from Indonesia, were identified as promising candidates for microplastic bioremediation. The novelty of this study the comprehensive integration of current evidence on microplastic contamination in Indonesian agroecosystems with a critical evaluation of its ecological risks and implications for sustainable agriculture. Furthermore, this study provides new perspectives on the potential role of fungi as bioremediation agents for microplastic contaminants. The findings provide a scientific basis for future research focusing on indigenous fungal isolates and microplastic degradation mechanisms as effective and sustainable strategies for environmental management.